DNA fragmentation in spermatozoa and its relationship with impaired spermatogenesis - S. A. Rudneva; E. E. Bragina; E. A. Arifulin; T. M. Sorokina; L. V. Shileyko; S. A. Ermolaeva; L. F. Kurilo; V. B. Chernykh (Андрология и генитальная хирургия, 2015)
Sperm cells DNA fragmentation is one of the factors of male sub-/infertility discovered recently. At present, pathophysiological mechanisms that cause DNA fragmentation have not been studied completely. It is suggested that they may be caused with defects of chromatin remodeling, apoptosis, and oxidative stress. Spermiological examination was performed in 461 infertile men. With 23 % of the patients examined, the frequency of sperm cells DNA fragmentation comprises over 15 %, with that, 18 % of the patients demonstrated its range from 15.1 to 30 %, and with 5 % of patients, it exceeded 30 %. We found that the amount of sperm cells with fragmented DNA with severe forms of pathozoospermia is higher that with less manifested disturbances of spermatogenesis. Negative dynamics was revealed regarding the change in sperm concentration in men that have increased frequency of DNA fragmentation. Obtained results confirm the suggestion of the correlation between some semen parameters (concentration, motility, and morphology) and sperm DNA fragmentation. Thus, one can state that the DNA fragmentation parameter of sperm cells has a certain diagnostic and forecasting value for married couples with reproduction disorders.